1999
DOI: 10.1143/jjap.38.1326
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of the MgSO4:Tb3+,Na+ Powder Phosphor

Abstract: MgSO 4 :Tb 3+ ,Na + powder phosphors were prepared by the solid-phase reaction. The obtained phosphors were stored in evacuated glass ampoules to prevent them from being converted into hydrous magnesium sulfate by the atmospheric moisture. The photoluminescence spectra and excitation spectra were obtained at 10, 80 and 300 K. Many narrow bands were observed in both the spectra, and were attributed to the transitions within the 4 f 8 electron configuration in Tb 3+ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, in LMB:Tb 3 þ by 377 nm excitation, emissions the in green region at 488 nm ( 5 D 4 -7 F 6 ), 541 nm ( 5 D 4 -7 F 5 ), 586 nm ( 5 D 4 -7 F 4 ) and 619 nm ( 5 D 4 -7 F 3 ) are only seen. The intensity of the 5 D 3 (blue) series is quenched by the cross-relaxation process between 5 D 3 -5 D 4 of the emitting Tb 3 þ and 7 F 6 -7 F 0 of the neighboring Tb 3 þ [25,26]. Gamma irradiations showed only negligible change in Tb 3 þ PL intensity, which means that redox process do not play any significant role in the TL of LMB:Tb 3 þ phosphors.…”
Section: Photoluminescence Spectramentioning
confidence: 95%
See 1 more Smart Citation
“…However, in LMB:Tb 3 þ by 377 nm excitation, emissions the in green region at 488 nm ( 5 D 4 -7 F 6 ), 541 nm ( 5 D 4 -7 F 5 ), 586 nm ( 5 D 4 -7 F 4 ) and 619 nm ( 5 D 4 -7 F 3 ) are only seen. The intensity of the 5 D 3 (blue) series is quenched by the cross-relaxation process between 5 D 3 -5 D 4 of the emitting Tb 3 þ and 7 F 6 -7 F 0 of the neighboring Tb 3 þ [25,26]. Gamma irradiations showed only negligible change in Tb 3 þ PL intensity, which means that redox process do not play any significant role in the TL of LMB:Tb 3 þ phosphors.…”
Section: Photoluminescence Spectramentioning
confidence: 95%
“…12. LMB:Tb 3 þ has the characteristic Tb 3 þ emission bands, minor peaks at 379, 412, 435, 487 and major emission at 544 nm due to electronic transitions 5 D 3 -7 F 6, 5 D 3 -7 F 5 , 5 D 3 -7 F 4, 5 D 4 -7 F 6 and 5 D 4 -7 F 5 , respectively [25,26]. After silver co-doping, minor emissions of Tb 3 þ are disappeared and major emission at 544 merged with host emission.…”
Section: Tl Emission Spectramentioning
confidence: 99%
“…Yamashita and Hamada [25] and Yamashita et al [26] observed the PL and TL spectra of the MgSO 4 :Tb 3 þ ,Na þ , CaSO 4 :Tb 3 þ ,Na þ , SrSO 4 :Tb 3 þ ,Na þ and BaSO 4 :Tb 3 þ ,Na þ powder phosphors. The PL and TL spectra of these phosphors consist of the very weak 5 D 3 and the prominent 5 D 4 series.…”
Section: Resultsmentioning
confidence: 99%
“…The emission peak at 541 nm ( 5 D 4 -7 F 5 ) was the highest among them, the reason is that this transition has the largest probability for both electric-dipole and magnetic-dipole transitions. The study on the narrow band peaks corresponding to the 5 D J -7 F J transitions within Tb 3 þ in different substrates has been widely reported: 5 D 3 -7 F 6 (380 and 382 nm), 5 D 3 -7 F 5 (414, and 416 nm), 5 D 3 -7 F 4 (436 nm), 5 D 3 -7 F 3 (456 nm), 5 D 4 -7 F 6 (488 nm), 5 D 4 -7 F 5 (545, and 548 nm), 5 D 4 -7 F 4 (587, and 589 nm) and 5 D 4 -7 F 3 (620, and 626 nm) [10][11][12]15,[21][22][23]. The emission intensity became higher with increasing TbF 3 concentrations from 0.1 to 1 wt%.…”
Section: Xrd Analysis Of the Samplesmentioning
confidence: 99%
“…Aierken et al [10] studied the PL properties of Na 2 SO 4 :RE 3 þ (Ce 3 þ , Sm 3 þ , Tb 3 þ , Dy 3 þ and Tm 3 þ ) phosphors prepared of natural thenardite, and reported the emission bands corresponding to the 5 D 3 -7 F J (J¼ 6, 5, 4, 3 and 2) and 5 D 4 -7 F J (J¼ 6, 5, 4, 3, 2, 1 and 0) transitions within Tb 3 þ . Yamashita and Hamada [11] and Yamashita [12]reported the PL properties of the MgSO 4 :Tb 3 þ , Na þ powder phosphor as well as PL and thermoluminescence of MgSO 4 , CaSO 4 , SrSO 4 , and BaSO 4 powder phosphors activated with Tb 3 þ . Song [13] studied the luminescent properties of Tb 3 þ -doped nano-ZnO, and reported that the best sample preparation parameters were obtained through the relationship between the characteristic green emission intensities and Tb 3 þ concentrations and annealing temperature.…”
Section: Introductionmentioning
confidence: 99%